The incidence of kryptoracemic crystallization in [CoIII(tren)XY]+ compounds: The case of cis-[CoIII(tren)Cl2]Cl·H2O - Mikhael, Mina; Hanna, Mary; Halaka, Evana; Bernal, Ivan; Lalancette, Roger (European Journal of Chemistry, 2020)
We are evaluating the proposition that compounds with pronounced tendencies to crystallize as kryptoracemates contain molecular fragments responsible for such a property. Why Sohncke space groups display such a tendency is not currently known, but one such fragment is the [tris(2-aminoethyl)amine-N,N',N'',N'''] ligand when attached to cobalt(III). Therefore, proceeding to test the concept further, we examined the title compound and found a previously unknown kryptoracemic species, described in what follows. It seems then that the prescription has some merit and should be examined further inasmuch as guidelines for the occurrence of kryptoracemic crystallization are scant, if any exist. Crystal data for C6H20Cl3CoN4O: monoclinic, space group P21 (no. 4), a = 7.6672(3) Å, b = 15.7153(5) Å, c = 10.7170(4) Å, β = 92.964(2)°, V = 1289.59(8) Å3, Z = 4, T = 100(2) K, μ(CuKα) = 16.026 mm-1, Dcalc = 1.697 g/cm3, 13406 reflections measured (8.26° ≤ 2Θ ≤ 133.402°), 3976 unique (Rint = 0.0300, Rsigma = 0.0519) which were used in all calculations. The final R1 was 0.0220 (I > 2σ(I)) and wR2 was 0.0459 (all data).